2005
DOI: 10.1128/jvi.79.20.13082-13093.2005
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Tegument Protein VP22 Contains an Internal VP16 Interaction Domain and a C-Terminal Domain That Are Both Required for VP22 Assembly into the Virus Particle

Abstract: Many steps along the herpesvirus assembly and maturation pathway remain unclear. In particular, the acquisition of the virus tegument is a poorly understood process, and the molecular interactions involved in tegument assembly have not yet been defined. Previously we have shown that the two major herpes simplex virus tegument proteins VP22 and VP16 are able to interact, although the relevance of this to virus assembly is not clear. Here we have constructed a number of recombinant viruses expressing N-and C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 35 publications
5
44
0
Order By: Relevance
“…These 42 residues lie in conserved domain 1 of many alphaherpesvirus Vhs molecules, including those of HSV-2, cercopithecine herpesviruses 1 and 2, bovine herpesvirus 2, suid herpesvirus 1, pseudorabies virus, and equine herpesvirus 4. In contrast, the C-terminal conserved region of VP22 has been identified as important for membrane association, virion incorporation, and interaction with VP16 (3,15). We observed that D1(42)GFP had similar properties to full-length Vhs.…”
Section: Discussionmentioning
confidence: 51%
“…These 42 residues lie in conserved domain 1 of many alphaherpesvirus Vhs molecules, including those of HSV-2, cercopithecine herpesviruses 1 and 2, bovine herpesvirus 2, suid herpesvirus 1, pseudorabies virus, and equine herpesvirus 4. In contrast, the C-terminal conserved region of VP22 has been identified as important for membrane association, virion incorporation, and interaction with VP16 (3,15). We observed that D1(42)GFP had similar properties to full-length Vhs.…”
Section: Discussionmentioning
confidence: 51%
“…9A, WT). We have previously provided evidence to suggest that localization of VP22 to these complexes correlates with efficient assembly of VP22 into the virus structure (23). Hence, to determine the effect of abolishing gE binding on VP22 localization to these complexes, we next determined the localization of GFP-VP22 ⌬gEbind in Vero cells infected in the same manner and imaged 8 h after infection.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we and others have previously shown that HSV-1 VP22 interacts directly with a second tegument protein, namely, VP16 (13,33), an interaction that could provide an alternative route for VP22 to enter the virion. In a previous study, we concluded that the region of VP22 containing its VP16 interaction domain was required but not sufficient for optimal VP22 packaging into the assembling virion, with an additional C-terminal determinant also involved (23). We also demonstrated that the same region of VP22 that was required for virion packaging was essential to target the protein to its characteristic cytoplasmic trafficking complexes, suggesting that these specific sites may be the location in the cell for VP22 assembly into the virion (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the UL48 (VP16) transcription factor associated with UL49 (VP22) and supported virus assembly (152), the knock out of UL49 (VP22) had no effects on the expression levels of the immediate early viral protein ICP0 (153), indicating that UL49 (VP22) has no important role for nuclear import of HSV1 DNA.…”
Section: Gtp and Other Factors (149) Experiments With The Hamster Mumentioning
confidence: 99%